The Private Practice of Prosthodontists: Current and Future Conditions of Practice in the United States (Part 2) - Kent D. Nash, PhD;1 and David L. Pfeifer, DDS, MS, MEd2 (Journal of Prosthodontics, 2007)
Data are used to examine current and future conditions important to the private practice of prosthodontics